Olfactory Exposure to β-Caryophyllene Increases Testosterone Levels in Women's Saliva - Wataru Tarumi, PhD; Kazuyuki Shinohara, PhD, MD (Sexual Medicine, 2020)
Introduction: From previous studies, we hypothesized that olfactory exposure to β-caryophyllene stimulates women's libido. However, Japan's sex culture is so closed that it is difficult to test this possibility without accumulating scientific evidence. Therefore, it is necessary to measure the concentration of sex-related hormones in saliva, an experimental technique that is relatively easy to obtain research permission, and to obtain a scientific basis to convince ethics committee reviewers. Aim: The aim of this study is to investigate whether β-caryophyllene increases salivary testosterone concentrations associated with libido and vaginal sensation during intercourse in women. Methods: 19 women in the follicular phase of the menstrual cycle participated in the study. The subjects then sat in front of the odor exposure device we had created. Each subject was exposed to dipropylene glycol for 20 minutes, followed by 3% β-caryophyllene for 20 minutes. Saliva was collected 4 times: before and after control exposure, and before and after β-caryophyllene exposure. Main Outcome Measure: Salivary testosterone and estrogen concentrations were measured with a competition ELISA. Results: β-caryophyllene significantly increased the salivary concentration of testosterone (control vs β-caryophyllene; 0.97 ± 0.05 vs 1.13 ± 0.03, P = .00, 95% confidence interval of control: 0.84–1.09, 95% confidence interval of β-caryophyllene: 1.04–1.20) but not estrogen (control vs β-caryophyllene; 1.05 ± 0.03 vs 1.07 ± 0.04, P = .69, 95% confidence interval of control: 0.96–1.12, 95% confidence interval of β-caryophyllene: 0.98–1.15). Strengths & Limitations: The personal preferences of the subjects and the order of exposure may have affected the results. Conclusion: β-caryophyllene may be a remedy with fewer side effects for women with decreased libido. We believe that β-caryophyllene may be a remedy for women with decreased libido. However, this hypothesis must be tested by further clinical studies.Wataru Tarumi, Kazuyuki Shinohara. Olfactory Exposure to β-Caryophyllene Increases Testosterone Levels in Women's Saliva. J Sex Med 2020;8:525–531.